A Colorimetric and Fluorimetric Chemodosimeter for Copper Ion Based on the Conversion of Dihydropyrazine to Pyrazine. Issue 1 (2nd October 2015) - Li, Junbo; Chen, Shao; Zhang, Pian; Wang, Zilong; Long, Guankui; Ganguly, Rakish; Li, Yongxin; Zhang, Qichun
Abstract: In this research, we successfully synthesized and fully characterized the new compound 5, 8, 13, 16, 21, 24‐hex‐(triisopropylsilyl)ethynyl)‐6, 23‐dihydro‐6, 7, 14, 15, 22, 23‐hexaza‐trianthrylene (HHATA, brown color in a mixed solvent of CH2 Cl2 /CH3 CN 1:1, v/v, weakly blue fluorescent), which can be easily oxidized to 5, 8, 13, 16, 21, 24‐hex‐(triisopropylsilyl)ethynyl)‐6, 7, 14, 15, 22, 23‐hexazatrianthrylene (HATA ) (yellow color in CH2 Cl2 /CH3 CN 1:1, v/v), red fluorescent) by Cu 2+ ions. This reaction only proceeds efficiently in the presence of Cu 2+ ions when compared with other common metal ions such as Fe 3+, Co 2+, Mn 2+, Hg 2+, Ni 2+, Pb 2+, Ag +, Mg 2+, Ca 2+, K +, Na +, and Li + . Our result suggests that this reaction can be developed as an effective method for the detection of Cu 2+ ions. Abstract : HHATA yoga : 5, 8, 13, 16, 21, 24‐Hex‐(triisopropylsilyl)ethynyl)‐6, 23‐dihydro‐6, 7, 14, 15, 22, 23‐hexazatrianthrylene (HHATA ) is weakly blue fluorescent and can be easily oxidized to the strongly red fluorescent 5, 8, 13, 16, 21, 24‐hex‐(triisopropylsilyl)ethynyl)‐6, 7, 14, 15, 22, 23‐hexazatrianthrylene (HATA ) by Cu 2+ ions. Thus, this reaction can be developed as an effective method for the detection of Cu 2+ ions.